2016
DOI: 10.1038/srep38662
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Salivary Oxytocin Levels and Generosity in Preschoolers

Abstract: This study examined the association between salivary oxytocin (sOT) levels and generosity in preschoolers. Fifty preschoolers played two dictator games (DG) by deciding how to allocate 10 chocolates between themselves and another child, who was either from the same class as the participant (ingroup member), or an unknown child from another class (outgroup member). sOT levels were assessed in saliva collected from the children immediately prior to the DG tasks. While sOT levels were negatively associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 62 publications
0
22
0
1
Order By: Relevance
“…This result is congruent with research in rhesus monkeys describing an association between central OT levels at 18 months and the expression of affiliative social behaviour with peers including allo-grooming, sitting in contact, clinging, and touching (69). Nevertheless, one study examining the association between salivary OT and generosity at these ages suggested that, similar to observations of adult monkeys(70), some degree of sexual dimorphism may exist regarding, at least, the association between OT and generosity: the association between OT and generosity tends to be stronger for girls than boys (67). Thus separate analyses by sex are needed to more fully characterize the role of OT socio-emotional behaviour and related neurocorrelates during childhood and adolescence.…”
Section: Preschool and School Childrenmentioning
confidence: 85%
“…This result is congruent with research in rhesus monkeys describing an association between central OT levels at 18 months and the expression of affiliative social behaviour with peers including allo-grooming, sitting in contact, clinging, and touching (69). Nevertheless, one study examining the association between salivary OT and generosity at these ages suggested that, similar to observations of adult monkeys(70), some degree of sexual dimorphism may exist regarding, at least, the association between OT and generosity: the association between OT and generosity tends to be stronger for girls than boys (67). Thus separate analyses by sex are needed to more fully characterize the role of OT socio-emotional behaviour and related neurocorrelates during childhood and adolescence.…”
Section: Preschool and School Childrenmentioning
confidence: 85%
“…C ν is counted in Ref. [50] rigorously up to ν = 14, which indicates that we can reduce p fault 0 by decreasing p sufficiently. The probability p fault l ′ of obtaining the level-l ′ faulty qubit is given recursively by…”
Section: Appendix C: Acceptance Probabilitymentioning
confidence: 97%
“…It is straightforward to generalize the following argument to any local CPTP noise as long as the noise strength measured by the diamond norm is sufficiently smaller than a certain threshold value [50]. Then the standard counting argument of the self-avoiding walk for the surface code [42] tells us that…”
Section: Ifmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some of this complexity may be accounted for by gender differences. Studies reporting that oxytocin increases or is positively associated with prosocial behavior also show that this effect is particularly robust for female children [78] and adults [7981], compared to males. However, not all studies report gender differences in the effect of oxytocin on prosocial behavior [75, 76].…”
Section: Oxytocin and Testosteronementioning
confidence: 99%